STUDY OF DISTRIBUTION OF SOME HEAVY METALS IN THE SOILOF BASRA CITY- SOUTH OF IRAQ - Khwedim, Kareem; Al- Anssari, Habib; Al- Bassam , Khaldoun (Iraqi Journal of Science, 2024)
The Objective of the present work is to estimate the concentration levels of someheavy metals (Cd, Co, Cr, Fe, Ni and Pb) in the soil of Basra city- south of Iraq andindicating to the probable pollution resources with these heavy metals. To achievethis aim (35) soil samples were collected from all over Basra city as well ascomparing the concentrations of the heavy metals in soil of Basra city with theirconcentrations in soils taken from (6) rural regions (Diayla, Haditha, Sinjar, Kirkuk-Musol road, Basra-Kut road, south of Emmara city) which are far away from thesources of pollution. Soil samples includes( industrial, commercial, residential andagricultural) areas (one sample for each area) with a depth(5-15) cm. preparation of samples after collecting for measuring by atomic absorptionspectrophotometer(AAS) was conducted. After getting the results, comparing withthe international limits for heavy metals in soil was done. Then contour maps weremade that revealed the distribution of studied heavy metals in the Basra city.From the results we can found that most of heavy metals (Pb, Ni, Cr and Cd)increasing to the west of Basra city because of its closeness from the petroleumestablishments like oil refinery of Al-Sha’eiba because the industrial waste of theseindustries contains high concentration of some heavy metals. There is alsoincreasing in the concentration of some studied metals soil in the middle of Basracity especially Al-Jazzaer area which consider as a commercial area suffering fromhigh traffic motion for automobiles and vehicles, like(Pb) as a by-product releasedfrom combustion of fuel due to the addition of (tetraethyl lead) to fuel as antiknockingagent. Then its cause an increasing of (Pb) in the atmosphere thenprecipitate on the soil, whereas decreasing of studied heavy metals was found to theeast of Basra city which is consider as an agricultural area and have well vegetariancover and far away from the industries establishments.